Hyperhomocysteinemia is associated with severity of cirrhosis and negative impact after liver transplantation. (5th November 2015) - Bhanji, Rahima A.; Ma, Mang; Bain, Vincent G.; Montano‐Loza, Aldo J.
Abstract: Background & Aims: Hyperhomocysteinemia constitutes an independent risk factor for thrombosis and cellular injury promoted by oxidative stress. The clinical significance of hyperhomocysteinemia in cirrhosis and outcomes post‐liver transplantation is poorly documented. In this study, we aimed to determine the prevalence of hyperhomocysteinemia in cirrhosis, evaluate its association with thrombosis and severity of liver disease, and its impact on survival after liver transplantation. Methods: We analysed 450 patients with cirrhosis who received a liver transplant between 2001 and 2010. Data were recovered from medical charts and homocysteine serum levels were determined before liver transplantation in all patients. Results: Median age was 53 years (range, 18–72 years) and 308 patients were males (68%). Cirrhosis aetiology was hepatitis C (37%), autoimmune liver disease (22%), alcohol (16%) and others (25%). The median homocysteine level was 11 μmol/L (range, 4–221 μmol/L) and 165 patients (37%) had hyperhomocysteinemia. The MELD (23 ± 10 vs. 20 ± 9 points, P < 0.001), and Child–Pugh (11 ± 2 vs. 9 ± 2 points, P < 0.001) scores were higher in patients with hyperhomocysteinemia. Episodes of thrombosis occurred in 91 patients (20%), but there was no significant difference in patients with or without hyperhomocysteinemia (19 vs. 21%, P = 0.6). Hyperhomocysteinemia was associated with reduced graft (105 ± 4 vs. 119 ± 2 months; P = 0.005), and patient survival (125 ± 33 vs. 131 ± 2 months; P = 0.006). Conclusions: Hyperhomocysteinemia is frequently present in patients with cirrhosis and is associated with severe liver disease and reduced graft and patient survival after liver transplantation. The negative impact hyperhomocysteinemia has on graft and patient survival is not related to thrombosis.